2005
DOI: 10.1158/0008-5472.can-04-2961
|View full text |Cite
|
Sign up to set email alerts
|

Combined Genetic Assessment of Transforming Growth Factor-β Signaling Pathway Variants May Predict Breast Cancer Risk

Abstract: There is growing evidence that common variants of the transforming growth factor-beta (TGF-beta) signaling pathway may modify breast cancer risk. In vitro studies have shown that some variants increase TGF-beta signaling, whereas others have an opposite effect. We tested the hypothesis that a combined genetic assessment of two well-characterized variants may predict breast cancer risk. Consecutive patients (n = 660) with breast cancer from the Memorial Sloan-Kettering Cancer Center (New York, NY) and healthy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 36 publications
(44 reference statements)
4
81
0
Order By: Relevance
“…Thus, it is feasible that the combination of the TGFB1 -509C/T and TGFBR2 -875A/G gene polymorphisms confer a synergistic effect on gastric cancer initiation and progression. This result confirmed the hypothesis that a combined assessment of functionally relevant common variants may aid in the characterization of cancer risk and prediction of disease aggressiveness (25).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, it is feasible that the combination of the TGFB1 -509C/T and TGFBR2 -875A/G gene polymorphisms confer a synergistic effect on gastric cancer initiation and progression. This result confirmed the hypothesis that a combined assessment of functionally relevant common variants may aid in the characterization of cancer risk and prediction of disease aggressiveness (25).…”
Section: Discussionsupporting
confidence: 83%
“…Several genetic polymorphisms exist in the TGF-b1 gene, one of which is a T-C transition at nucleotide 29 of the coding region, resulting in a leucine to proline substitution at codon 10 (Blobe et al, 2000;Breast Cancer Association Consortium, 2006;Cox et al, 2007). This single nucleotide polymorphism (SNP) T29C, which is in strong linkage disequilibrium with another common SNP C-509T, has been studied extensively for its association with breast cancer risk and survival (Yokota et al, 2000;Goode et al, 2002;Hishida et al, 2003;Krippl et al, 2003;Ziv et al, 2003;Jin et al, 2004;Le Marchand et al, 2004;Shu et al, 2004;Kaklamani et al, 2005;Lee et al, 2005;Shin et al, 2005;Skerrett et al, 2005;Breast Cancer Association Consortium, 2006;Feigelson et al, 2006;Gonzalez-Zuloeta Ladd et al, 2007). Two studies found increased risk of breast cancer among Koreans and Dutch who carry the C allele (Lee et al, 2005;Gonzalez-Zuloeta Ladd et al, 2007), whereas two other studies showed decreased risk in relation to C genotype among Americans who were older than 65 years or Japanese who were premenopausal (Hishida et al, 2003;Ziv et al, 2003).…”
mentioning
confidence: 99%
“…TβRI mutations occur less frequently than TβRII mutations, and have been reported most often in ovarian, pancreatic and cervical carcinomas, as well as in some lymphomas (Elliott and Blobe, 2005;Seoane, 2006). TβRI signal sequence mutations have also been reported in breast and colorectal cancers Kaklamani et al, 2005). The TβRI*6A mutation most commonly reported enables cancer cells to resist the cytostatic action of TGF-β Pasche et al, 2005).…”
Section: Inactivation Of the Tgf-β Signaling Pathwaymentioning
confidence: 99%